Seasonal Variation and Its Impact on Rice Price Adjustment in Tasikmalaya City - Januar Ruslan; Dira Pramita (PT FORMOSA CENDEKIA GLOBAL, 2023)
Changing marketing margins through speed of price adjustments is an indicator of efficient markets. This research analyzes differences in price adjustments according to rice quality based on production period in Tasikmalaya City. Data used is weekly price at wholesalers and retailers from January 2019 to January 2022. Analysis uses an independent sample t-test to compare rice price adjustments based on harvest and non-harvest times. Results show, price adjustment responses tend to be different, especially for low and medium-quality rice at harvest period, while premium quality shows same price adjustment response. During non-harvest period, price adjustment response tends to be same for all rice. Application of basic prices is not only at producer prices but also in other rice marketing channels especially at harvest period.